Host-encoded, cell surface-associated exopolysaccharide required for adsorption and infection by lactococcal P335 phage subtypes - Millen, Anne M.; Romero, Dennis A.; Horvath, Philippe; Magill, Damian; Simdon, Laura (Frontiers in Microbiology, 2022)
Lactococcus lactis and Lactococcus cremoris compose commercial starter cultures widely used for industrial dairy fermentations. Some lactococcal strains may produce exopolysaccharides (EPS), which have technological applications, including texture production and phage resistance. Two distinct gene clusters associated with EPS production, designated 6073-like and 7127-like, were identified on plasmids in lactococcal strains. Infectivity of two subsets of P335 group phages, distinguished based on their single-component baseplate/receptor binding protein nucleotide sequences, was correlated to the presence of a host-encoded 6073-like or 7127-like eps gene cluster. Furthermore, phages belonging to these subsets differentially adsorbed to lactococcal strains harboring the respective eps gene cluster. Loss of the respective EPS-encoding plasmid from a fully phage-sensitive strain resulted in loss of phage adsorption and resistance to the phage. Transmission electron microscopy showed that the EPS produced by strains encoding the 6073-like or 7127-like eps gene clusters are cell-surface associated, which, coupled with phage plaquing and adsorption data, shows that specific capsular EPS are involved in host recognition by certain P335 phage subgroups. To our knowledge this is the first description of the involvement of EPS produced via the Wzx/Wzy-dependent pathway in phage sensitivity of L. lactis or L. cremoris. This study also shows strains that do not appear to be phage-related based on plaque formation may still be related by phage adsorption and indicates that optimal formulation of phage-robust cultures should take into account the EPS type of individual strains.